EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI PADI PETANI YANG MENDAPAT DAN TIDAK MENDAPAT PROGRAM UPSUS PAJALE (STUDI KASUS DI DESA SEBALIK KABUPATEN BANYUASIN) - Yesi, Desri; Mulyana, Andy; Riswani (Agripita Publisher, 2018)
The special efforts to increase rice, corn and soybean production Program (Upsus Pajale Program) that started in 2015 is one of the government's strategic programs in achieving national food security, so it is necessary to evaluate the extent of its success. This study analyzes factors that affect production levels, the efficiency of production and income of the rice farming which is involved or not involved in Upsus Pajale Program. The data consisted of primary and secondary data source. The sampling method used a disproportionale stratified random sampling method. To answer the research objectives used Cobb-Douglass production function, efficiency calculation and T-test. The result of data processing sho(wed that the rice farming which is involved in Upsus Pajale Program that: labor factor, Urea, NPK and pesticide were influenced the production, while the land, SP-36 and seed weren’t. The rice farming which is not involved in Upsus Pajale program showed that all of production factors weren’t influenced on production. The efficiency of rice farming which is involved in Upsus Pajale Program indicates that land, SP 36 and NPK are not efficient while labor, urea, pesticide and seed are efficient for technically, allocatively and economically. In rice farming which is not involved in Upsus Pajale program, the use of land and SP 36 are not efficient while labor, urea, NPK, pesticide and seed are efficient for technically, allocatively and economically. The results of the data processing also showed that income average between the two samples were difference.